2021
DOI: 10.1038/s41420-021-00451-x
|View full text |Cite
|
Sign up to set email alerts
|

A novel defined pyroptosis-related gene signature for predicting the prognosis of ovarian cancer

Abstract: Ovarian cancer (OC) is a highly malignant gynaecological tumour that has a very poor prognosis. Pyroptosis has been demonstrated in recent years to be an inflammatory form of programmed cell death. However, the expression of pyroptosis-related genes in OC and their correlations with prognosis remain unclear. In this study, we identified 31 pyroptosis regulators that were differentially expressed between OC and normal ovarian tissues. Based on these differentially expressed genes (DEGs), all OC cases could be d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
365
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 355 publications
(373 citation statements)
references
References 37 publications
7
365
1
Order By: Relevance
“…Our research was conducted without ethical examine given that the entire data were accessible openly. Our team chose an overall 33 pyroptosis-associated genes as per past research [7,10].…”
Section: Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our research was conducted without ethical examine given that the entire data were accessible openly. Our team chose an overall 33 pyroptosis-associated genes as per past research [7,10].…”
Section: Data Collectionmentioning
confidence: 99%
“…Pyroptosis is a cell death triggered by caspase-1/4/5/11 and results in cell swelling, chromatin fragmentation ,plasma membrane cleavage, and intracellular proin ammatory release [5]. More and more studies showed that pyroptosis is vital for the cancer progress.Some previous studies reported that some key components of pyroptosis,such as in ammatory vesicles, proin ammatory cytokines ,and gasdermin proteins are closely related to tumourigenesis, invasion, and metastasis [6,7]. A few latest studies con rmed that pyroptosis play a critical role in tumour immune microenvironment and antitumour processes as well [8,9].…”
mentioning
confidence: 99%
“…We identi ed 4,851 and 6,513 DEGs in the LUAD and LUSC cohorts, respectively (Table S1). Subsequently, 40 and 45 pyroptosis-related genes were identi ed from the LUAD and LUSC cohorts, respectively, based on a previous review [41][42][43][44] (Table S2).…”
Section: Data Preparationmentioning
confidence: 99%
“…The previous review contributed 33 PRGs to our research [10][11][12]. Protein-Protein Interaction Networks (PPI) of 33 PGRs were presented in Fig.…”
Section: Data Preprocessingmentioning
confidence: 99%
“…Several risk-related signaling molecules and cytokines are activated and disseminated after pyroptosis, resulting in a signi cant in ammatory cellular response and immune system activation [9]. Pyroptosis has a signi cant pro-in ammatory effect that is linked to the control of the tumor immune microenvironment, which is crucial for tumor growth [10]. Moreover, despite the fact that pyroptosis has been linked to cancer in numerous studies, the relationship between pyroptosis and anticancer immunity is still a mystery [9].…”
Section: Introductionmentioning
confidence: 99%